Facile synthesis of copper ferrocyanide-embedded magnetic hydrogel beads for the enhanced removal of cesium from water. (June 2019) - Lee, Inae; Park, Chan Woo; Yoon, Seung Soo; Yang, Hee-Man
Abstract: A simple one-step approach for fabricating copper ferrocyanide-embedded magnetic hydrogel beads (CuFC-MHBs) was designed, and the beads were applied to the effective removal of cesium (Cs) and then magnetically separated from water. The polyvinyl alcohol (PVA)-coated CuFC (PVA-CuFC) was first synthesized using PVA as a stabilizer and subsequently embedded in magnetic hydrogel beads made of a cross-linked network between the PVA and magnetic iron oxide nanoparticles that was prepared through the simple dropwise addition of a mixed solution of PVA-CuFC, PVA and iron salt into an ammonium hydroxide solution. The synthesis and chemical immobilization of the PVA-CuFC in the magnetic beads were simple, facile and achieved in one pot, and the process is scalable and convenient for the large-scale treatment of Cs-contaminated water. The resulting CuFC-MHBs showed effective Cs removal performance with a high Kd value of 66, 780 mL/g and excellent structural stability without the release of CuFC for at least 1 month and could be effectively separated from water by an external magnet. Moreover, the CuFC-MHBs selectively adsorbed Cs with high Kd values in the presence of various competing ions, such as in simulated groundwater (24, 500 mL/g) and seawater (8290 mL/g), and maintained their Cs absorption ability in a wide pH range from 3 to 11. The convenient fabrication method and effective removal of Cs from various aqueous media demonstrated that the CuFC-MHBs have great potential for practical application in the decontamination of Cs-contaminated water sources caused by nuclear accidents and radioactive liquid waste in various nuclear industry fields. Highlights: A facile one-pot synthesis of copper-ferrocyanide-embedded magnetic hydrogel beads was developed. CuFC-MHBs can be fabricated in a large quantity, which is crucial for their practical applications. The beads can remove Cs in a wide pH range from 3 to 11 with excellent structural stability for up to 1 month. The beads exhibit excellent selectivity for Cs, even in the presence of competing ions such as in groundwater conditions.